Barron's IELTS practice exams with audio CDs - Lougheed, Lin, 1946-; Barron's Educational Series, Inc. (Hauppauge, NY : Barron`s, 2013)
Provides sample questions and answers, self-study ideas, and six full-length practice exams.
Academic module -- General training module -- Audio scripts for listening -- How to use the audio CDs.
Previous edition: 2010.
English language and literature.
Keywords: International English Language Testing System -- Study guides; English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides; English language -- Sound recordings for foreign speakers